Civil society, democratic legitimacy and the European Union: democratic linkage and the debate on the future of the EU - Monaghan, Elizabeth (2007)
Recent reform agendas have emphasised a perceived need to bring the European Union (EU) institutions and the citizens of the member states and closer together, as a means of enhancing the legitimacy of EU governance. The debate on the future of the EU, the initiative which led to the signing of the constitutional treaty in October 2004, addressed the challenge of 'bringing closer' by incorporating civil society in to the treaty reform process. In this thesis I investigate the role played by transnational civil society organisations in helping to bring citizens and institutions closer together. I employ the notion of democratic linkage to describe and explain the downward-facing interactions between civil society organisations and ordinary citizens, which have sometimes been neglected, as well as their upward-facing interactions with elite decision-makers. Drawing upon data from qualitative interviews with 25 civil society organisations and six officials from various EU institutions I find serious discrepancies between the rhetoric of the EU institutions on bringing citizens closer, and the capacities and willingness of the civil society actors involved as well as the opportunities for doing so.